The essential guide to image processing - Bovik, Alan C. (Alan Conrad), 1958- (Academic Press, 2009)
This comprehensive and state-of-the art approach to image processing gives engineers and students a comprehensive introduction, and includes full coverage of key applications: image watermarking, fingerprint recognition, face recognition and iris recognition and medical imaging. To help learn the concepts and techniques, the book contains a CD-ROM of 70 highly interactive visual demonstrations. Key algorithms and their implementation details are included, as are the latest developments in the standards.* A complete and modern introduction to the basic and intermediate concepts of image.